IMPLICATIONS OF SUPERVISION OF GOVERNANCE, OWNERSHIP STRUCTURE, AND CORPORATE SOCIAL RESPONSIBILITY ON PROFITABILITY IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Muhammad Taufik; Jonathan Jonathan (Berkala Akuntansi dan Keuangan Indonesia, 2021)
This study investigates the implications of governance characteristics oversight - consisting of board of commissioners independent, audit committees number, institutional ownership, and managerial ownership and corporate social responsibility (CSR) on profitability. The regression technique uses panel data with 2,060 data from all types of industries listed on the Indonesia Stock Exchange in 2015-2019. Managerial ownership and CSR have a positive and significant effect on return on assets (ROA) so that they are considered to reduce agency costs. In contrast, board of commissioners independent, audit committees number, and institutional ownership have no effect on ROA thus confirming the decline in corporate governance in Indonesia. Implications of this study contributes to showing the existence of governance regulations "which are only fulfilled" without giving substance and emphasizes that social aspects exist in corporate stakeholder studies.